The distribution of income and expenditure in the budget of the People’s Republic of Tuva, 1929-1943 - Taibyl, Regina S. (The New Research of Tuva, 2016)
In the history of Tuva during the period of its relative independence (1921-1944, when it was known as the People’s Republic of Tuva (PRT)), economic historians find special interest in the study of the republic’s budget. Although Russian historians made a significant contribution into this field, the distribution of PRT’s budget has never been studied in its entirety throughout all of the years of the republic’s history. The aim of this article is to reconstruct the PRT’s budget distribution for the years 1929-1943 (the period which have not explored in detail before). Our study is based on archival sources, namely, budget reports of PRT’s Ministry of Finance which are preserved at the State Archives of the Republic of Tuva. The ministry never submitted to the archives any data for 1944 (the last year before PRT became part of the USSR).To follow the dynamics of budget development, we have studied the materials published by A.G. Kovalev, L.I. Tul’chinskii, A.I. Kaplunov, authors of “Istoriia Tuvy” (2001, 2007), N.P. Moskalenko and D.F. Dabiiev. Their data are summed up in the table provided in the article. An analysis of their works has shown that these authors have actually relied on the figures for PRT’s early years only.The archival documents analyzed in the article provided the data for another table which shows that in 1929-1931 there were 4 articles of income and expenditure in the PRT’s budget. Treading in the footpath of the Soviet Union, the PRT adopted a surplus budget, with incomes exceeding expenditures and turning over into the following year. The incomes of the budget kept increasing, and the main articles were expenditure were the national economy, social and cultural policy and national administration, courts and prosecution office.The research field can obviously be further expanded by studying the issues related to specific articles of PRT’s budget.
Keywords: history of Tuva; People’s Republic of Tuva; economy; fiscal policy; bugdet; finance